Recent Data of Extensive Air Showers Recorded by Alborz I Array and Their Detailed Analysis - Mahmud Bahmanabadi; Mostafa Heydarizad (Iranian Journal of Astronomy and Astrophysics)
An array of five scintillation detectors has been installed in Sharif University of Technology to record extensive air showers. ‎‎‎By using the time lags of the secondary particles of air showers relative to each other and the location of each of these ‎particles‎ relative to the core of the shower, the arrival direction of the primary particle producing each air shower has been ‎obtained.‎‎‎These data show that the distribution of time intervals of successive events in all directions of arrival into‎ the atmosphere is a random distribution‎. The distribution of the time intervals between successive events in different ‎seasons‎ has also been obtained and the seasonal effect has been ‎investigated‎. The effects of the environment‎, ‎including temperature and pressure‎, on the cosmic ray count rate have been investigated‎. ‎The distribution of zenith and azimuth angles‎, ‎as well as‎ the ‎solar,‎ sidereal, and antisidereal time distributions of cosmic rays‎, ‎have been obtained‎.